Życie publiczne a moralność - Hułas, Maciej (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Public life involves a variety of actions ordinary people undertake within the interstitial domain, located between the private realm of households and the institutional area of the state. Although public life was commonly cultivated in the ancient times as a way to attain stages of refined emancipation, its contemporary forms stem from the modern bourgeois culture. Owing to the fact, that public life plays out around issues that are of crucial significance for the proper existence of individuals and groups, it becomes a field of particular moral responsibility. Responsible actions in the public realm demand a stable disposition of adopting all available means for improving the social subsystems, particularly those which directly fall under civic scrutiny: politics and culture